Cut-Rate Genomes on the Horizon? - Pennisi, Elizabeth; Shendure, J. (Science (American Association for the Advancement of Science), 2005)
Given the exorbitant cost of deciphering genomes, most labs have given up sequencing and left that job to the big sequencing centers. But now, two groups have published methods that may be much cheaper and faster, promising small labs a chance to do more of their own sequencing.